Digitalis - Kendig, Ronie (Kendig, Ronie. Discarded heroes, 2011)
"Colton Neeley left his military career to take care of his four-year-old daughter. Although he's firm in his faith now, the repercussions of his former life are still evident--namely in the form of his daughter and his debilitating flashbacks from combat-related trauma. Can he muster the courage to step out of his self-imposed isolation and embrace the new woman in his life? Piper Blum is hiding--from life and the assassins bent on destroying her family. Although smitten by Colton, she fears the day he discovers her secrets. Does their relationship, built on a foundation of lies, have a chance? When an attempt on Piper's life leads to another's death, the black ops group Nightshade steps into the line of fire. Will Colton and Piper survive the mission with the love--and lives--intacts? Will love cover their multitude of sins?"--P. [4] of cover.